Competitive asymmetry and local adaptation in Trinidadian guppies. Issue 2 (26th November 2018) - Potter, Tomos; King, Leighton; Travis, Joseph; Bassar, Ronald D.
Abstract: The outcome of competition between individuals often depends on body size. These competitive asymmetries can drive variation in demographic rates, influencing the ecology and evolution of life histories. The magnitude and direction of such asymmetries differ among taxa, yet little is known empirically about how adaptation to resource limitation alters competitive asymmetries. Here, we investigate the relationship between size‐dependent competitive ability and adaptation to resource limitation. We examined size‐dependent competition in two ecotypes of Trinidadian guppy, adapted to high or low levels of resource competition. Using aquaria‐based competition experiments, we describe how the size and ecotype of competitors influence somatic growth rate, whilst controlling for the confounding effect of niche differentiation. We replicated our study across two independent evolutionary origins of the "competitive" ecotype. The two "competitive" ecotypes differed markedly in size‐dependent asymmetry, indicating that adaptation to resource limitation alone is insufficient to explain changes in size‐dependent competitive asymmetry. For one origin, the ecotype adapted to resource limitation was a superior competitor over a wide range of size pairings. The equivalence of competitors varied over fivefold, dependent on size and ecotype; in three of four populations, larger individuals had a competitive advantage. Our results demonstrate that competitive asymmetry has strong effects on somatic growth. Because somatic growth contributes to demographic parameters, intraspecific trait variation is likely to play a key role in regulating demographic rates. Our findings imply that the evolution of size‐dependent asymmetries under conditions of intense competition is likely to be constrained by niche availability, although further research is needed to verify this. Abstract : Competition is often modelled as a function of population density: competitors are considered equal. The authors show that competitive equivalence between individuals can vary fivefold dependent on size and population in Trinidadian guppies. The traits of competitors have a significant effect on a key driver of demographic rates and somatic growth.